The Role of Computed Tomography in the Management of Chronic Rhinosinusitis - Athar Adnan Uppal, Saira Saeed, Nasir Riaz, Saira Zaman, Tabeer Arif, Aysha Nauman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic rhinosinusitis is a painful and debilitating condition that has been estimated to affect more than 10% to 15% of the world’s population. Pharmacological treatments for chronic rhinosinusitis still present some problems: symptoms are chronic and do not subside even after treatment. Objective: To evaluate the role of computed tomography in the management of chronic rhinosinusitis. Material and Methods: This prospective, cross-sectional study was carried out at Fatima Memorial Hospital and General Hospital, Lahore, Pakistan from 1st October 2014 to 30th June 2015. A total of 50 patients with sinonasal symptoms who were selected for a computed tomography of the nose and paranasal sinuses were enrolled. Persons with head injury or malignancy treated through irradiation were not included. Computed tomography images were performed on a Toshiba 16-slice helical computed tomography with slice thickness of 3mm in coronal, axial and sagittal planes. Results: The prevalence of deviated nasal septum was 32% while the inferior turbinate hypertrophy was 74%. Concha bullosa and nasal spur were seen in 22% of the specimens studied here. Ostiomeatal complex widening was noted in 70 % of the patients. Intraorbital involvement was found in 8% and intracranial spread was found in only 4% of the patients. Conclusion: Computed tomography imaging offers valuable information required for new and persistent chronic rhinosinusitis diagnosis and management. It is a guide for the surgeons and is the most definitive way of confirming disease. Keywords: Chronic rhinosinusitis, Computed tomography, Radiotherapy, Sinonasal, Osteomeatal